Peran Guru dalam Psikologi Perkembangan Anak Usia Dini - Yunus, Cantika Wulandari; Kuncoro, Muhamad Wahyu (Lembaga Intelektual Muda Maluku, 2025)
This study explores the important role of teachers in early childhood developmental psychology by drawing on the theoretical frameworks of figures such as Vygotsky, Bowlby, and Piaget. These developmental theories provide a broad perspective on how children learn and develop. The type of research used is library studies. This study focuses more on previous studies that examine the function of educators in the formation and development of developmental psychology theories. Data analysis is carried out qualitatively with the stages of data reduction, data presentation, and conclusion drawing. The results of the analysis show that a child's environment has a great influence on his development. The involvement of educators will be very effective in helping children's growth and development if children's growth and development go according to plan and in accordance with the child's age and developmental stage. There are many theories in developmental psychology, such as those put forward by Piaget, Bowbly, and Vygotsky. Preoperative thinking is present in children, according to Piaget's theory. Children have learned to use symbols for various objects and begin to interact with the surrounding environment in a fun and orderly way. Educators are highly responsible for guiding, encourage, and encouraging their children. Positive social interactions, appropriate stimulus, and a safe and supportive environment are important factors in the formation of personality and character